Cyberbullying: Pertanggungjawaban Pidana Anak Atas Hilangnya Nyawa Seseorang Ditinjau Berdasarkan Keadilan Restoratif - Ade Borami Ju; Eko Nurisman (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Currently cyberbullying is one form of crime that is quite often occur in cyberspace, especially among teenagers. Cyberbullying itself is one form of crime that can be reported to be further processed to the court. In dealing with the law, it can have a variety of influences, both mental, physical and social for children, especially if the problem is resolved through formal channels such as the court. Restorative justice is presented as an alternative path to solving criminal problems by involving victims, perpetrators, victims' families to jointly seek a fair solution by emphasizing recovery back to its original state, and not retaliation. The purpose of the study was to find out how criminal accountability of children as perpetrators of cyberbullying crimes resulting in the loss of a person's life based on restorative justice. This research uses normative juridical approach methods with data collection techniques using secondary data conducted with literature research. The conclusion of this study is the Legal Regulation against cyberbullying crimes consisting of regulations in the Criminal Code, Law No. 11 of 2012 on the Juvenile Criminal Justice System, and Law No. 19 of 2016 on Changes in Information and Electronic Transactions. Based on restorative justice, accountability for children perpetrators of cyberbullying crimes that result in the loss of one's life can be in the form of criminal sanctions and action sanctions. The criminal imprisonment of child offenders is used as a last resort, this is because the juvenile criminal justice system is carried out one of which is based on the principle of deprivation of independence and prosecution as a last resort.